Neuromuscular - Prahlow, Nathan D.; Kincaid, John C. (Rehabilitation medicine quick reference., 2014)
Designed for the busy practitioner, Neuromuscular provides succinct coverage of the assessment and treatment of a wide spectrum of neuromuscular diseases and conditions ranging from common to extremely rare and from relatively benign to universally fatal. Including more than 90 topics presented in a consistent format for maximum clinical utility, this nuts and bolts resource delivers point-of-care information for effectively managing peripheral nerve disorders and neuromuscular pathologies. The book is organized in seven broad sections covering mononeuropathies, polyneuropathies, the neuromuscular junction, motor neuron disease, radiculopathies and plexopathies, muscle diseases, and movement disorders. Within these sections the authors address the individual and varied diseases and syndromes that comprise the field of neuromuscular and electrodiagnostic medicine and offer a clinical roadmap for evaluation and treatment. With the improvement of function as the primary goal, the book focuses on diagnoses usually managed by neurologists and physiatrists and facilitates the relationship between these fields in the treatment of neuromuscular disease. Every entry is standardized for quick look-up in the office or clinic, and features description, etiology, risk factors, clinical features, natural history, diagnosis, red flags, treatment, prognosis, helpful hints, and suggested readings.